2018
DOI: 10.1016/j.jsat.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in outcomes among patients in the “Stimulant Abuser Groups to Engage in 12-Step” (STAGE-12) intervention

Abstract: Younger age was associated with larger treatment effects for stimulant use. Specifically, younger age was associated with greater odds of remaining abstinent from stimulants in STAGE-12 versus Treatment-as-Usual; however, among those who were not abstinent during treatment, younger age was related to greater rates of stimulant use at follow-up for those in STAGE-12 compared to TAU. There was no main effect of age on stimulant use. Younger age was also related to somewhat greater active involvement in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…A study found that this strategy could provide low- or no-cost options for MA users and increase the capacity for providing treatment (62). Moreover, research showed that the 12-step recovery could be better used for young drug dependent users (63). Our study showed that the onset age of MA use was about 23 years old and their average age was 33 years old.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that this strategy could provide low- or no-cost options for MA users and increase the capacity for providing treatment (62). Moreover, research showed that the 12-step recovery could be better used for young drug dependent users (63). Our study showed that the onset age of MA use was about 23 years old and their average age was 33 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates are often included in the analysis; these covariates may include latent psychological constructs that are not directly observable. In the field of drug and substance use prevention, the effects of interventions on the outcome variables daily/weekly count of alcoholic drinks or cigarettes consumed have been examined (Garrett et al, 2018;Neighbors et al, 2015) taking the covariates of readiness and social identity into account. Cognitive psychologists are often interested in how an intervention affects the counts of correctly-answered items on a cognitive test (Jobe et al, 2001;Nusser & Weinert, 2017), controlling for baseline mental abilities.…”
Section: Treatment Effects On Count Outcomes With Latent Covariatesmentioning
confidence: 99%